2018
DOI: 10.1155/2018/8941564
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect and Molecular Mechanism of [6]‐Gingerol against Scopolamine‐Induced Amnesia in C57BL/6 Mice

Abstract: We have investigated the neuroprotective and memory enhancing effect of [6]-gingerol (GIN), a pungent ingredient of ginger, using an animal model of amnesia. To determine the neuroprotective effect of GIN on cognitive dysfunction, scopolamine (SCO, 1 mg/kg, i.p.) was injected into C57BL/6 mice, and a series of behavioral tests were conducted. SCO-induced behavior changes and memory impairments, such as decreased alteration (%) in Y-maze test, increased mean escape latency in water maze test, diminished step-th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…Similarly, previous studies reported that 6G inhibited apoptosis in response to myocardial ischemia/reperfusion (I/R) injury as a possible mechanism to attenuate I/R-induced injury in the heart [8]. Besides that, the neuroprotective effects of 6G have been reported in scopolamine-induced amnesia in C57BL/6 mice [22]. However, to our knowledge, this is the first study to show that 6G exerted neuroprotective effects by suppressing hypoxia-induced apoptosis and autophagy in PC-12 cells.…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, previous studies reported that 6G inhibited apoptosis in response to myocardial ischemia/reperfusion (I/R) injury as a possible mechanism to attenuate I/R-induced injury in the heart [8]. Besides that, the neuroprotective effects of 6G have been reported in scopolamine-induced amnesia in C57BL/6 mice [22]. However, to our knowledge, this is the first study to show that 6G exerted neuroprotective effects by suppressing hypoxia-induced apoptosis and autophagy in PC-12 cells.…”
Section: Discussionmentioning
confidence: 73%
“…These changes can be seen in different regions of the brain in diabetes, namely, the frontal cortex, dentate gyrus, and cerebellum. The neuroprotective properties of ginger were confirmed by a previous study [96]. It was found that the oral administration of ginger extract to mice with SCO-induced memory loss upregulated the level of brain-derived neurotrophic factor (BDNF), which is essential to neuronal maintenance and survival, synaptic plasticity, and cognitive processes.…”
Section: Ginger As An Antioxidant Involved In Delaying Ageingmentioning
confidence: 55%
“…Normal animals will prefer to explore a different arm of the maze than the one they visited on their previous entry. This test is mostly used to assess hippocampal-dependent working memory [34]. Therefore, an animal with a memory deficit cannot recall which arm of the maze it has just visited and consequently will exhibit a lower percentage of alternation.…”
Section: Discussionmentioning
confidence: 99%